(untitled) (Publicatio UEPG: Ciências Sociais Aplicadas, 2024)
The article has a general objective to identify Public Hospitals in the South Zone of São Paulo that have a Palliative Care Commission, and a specific objective to identify units that have Official Regulations for public access. The investigation is justified by the practical exercise inherent to the Multiprofessional Residency in Clinical Emergencies and Trauma / Social Work in a Secondary Public Hospital in the South Zone of São Paulo. The service presents a considerable number of patients in Palliative Care, and this indication is made to patients who do not present curative prospects. The article has a quantitative/qualitative character, analyzing published studies, books, articles and electronic sites. The route revealed difficulties due to the lack of information, official websites and updated content. The results showed that 88.9% of public hospitals do not publicly display information on the subject under discussion and 11.1% indicated the performance of the Palliative Care Commission for users of Health Services.